How does the Goverment Legally Respond to the Cyber Attack? Cases in Australia, People's Republic of China, and India - Edho Aqmal Hakim (NEGREI: Academic Journal of Law and Governance, 2021)
In the 21stcentury, cyber attacks are one of the biggest threats to international peace. The aim of this paper are to compare responses of different governments in this case Australia, People's Republic of China and India. Literature study provides a variety of information that is processed by comparative analysis. Three countries have their own approach to answer this cyber attacks issue by founded their own cyber security agencies. In recent years, these countries were able to develop and integrated strong defense mechanism against cyber attacks. While international cooperation and international laws against cyber attacks have not yet to be born, applying multi layered defense of active and passive defenses in their own country is the best option to choose so far. However, each country needs to evaluate the impact of cyber attacks and whether their responses have been effective in dealing with these cyber attacks using quantitative analyzes.